A case in which immunohistochemistry was useful in the diagnosis of gastric metastasis of invasive lobular carcinoma. Issue 3 (25th March 2023) - Jinushi, Ryuhei; Sato, Ryo; Kawasaki, Tomonori; Ryozawa, Shomei
ABSTRACT: Metastatic breast cancer can spread to the bone, brain, liver and lung. However, metastasis to the stomach is rare. Gastric metastasis mostly presents within 10 years from the diagnosis of the primary breast cancer. We present a rare case of gastric metastasis occurring 20 years after mastectomy, diagnosed through immunohistochemistry.